Impact of microbial Nocardia vaccinii IMB B-7405 surfactants on oil destruction in water - Pirog, Tatiana; Panasiuk, Catherine; Antoniuk, Nina (My University, 2016)
The degree of oil degradation, as well as complex oil pollution with heavy metal in water in the presence of Nocardia vaccinii ІMV B-7405 biosurfactants was studied. The destruction of crude oil (2,6−6,0 g/l) in water) at 25−30 days after treatment with the post-fermentative culture liquid (5−10% v/v) containing biosurfactant was 76−94%.
Keywords: кафедра біотехнології і мікробіології; oil destruction; surfactants; heavy metals; Nocardia vaccinii IMB В-7405; деструкція нафти; поверхнево-активні речовини; важкі метали; деструкция нефти; поверхностно-активные вещества; тяжелые металлы